Phytogenic One-pot Synthesis and Spectroscopic Characterization of Novel Mono Benzylated Resveratrol Hybrid Molecule Using Extracted Resveratrol from Green Grape Peels: In Silico ADMET Study and In Vitro Antitumor Activities Against Breast Cancer Cells - Roy, Lairikyengbam D.; Kumar, Jyotsna; Krishnamurthy, Geeta; Gour, Pooja; Arland, Shivanjali Esther; Rahman, Naveed (Current Bioactive Compounds, 2023)
Background: Despite the development of numerous customized techniques for treating breast cancer, cancer patients' clinical results revealed adverse consequences in addition to chemotherapeutic drug resistance. Hence, finding therapeutic compounds with little or no side effects becomes essential in the fight against cancer. Resveratrol, a naturally occurring non-flavonoid polyphenol present in plants as a phytoalexin, is a promising therapeutic agent that has garnered the interest of several researchers due to its prodigious pharmacological and biological activities, but its unfavourable pharmacokinetic properties complicated its clinical studies. Along with several structural modifications, substitutions, etc., that have already been reported, this is the first time that a novel resveratrol analogue comprising an aromatic hetero moiety (ResD1) was synthesized using resveratrol isolated from grape (Vitis vinifera) peels as a precursor. Methods: ResD1 was synthesized by one-pot reaction using extracted and isolated resveratrol from grape peels. Structure confirmation of the isolated resveratrol and synthesized resveratrol derivative was elucidated by 1H-NMR, 13C-NMR, FTIR, and LC-MS. In silico molecular docking and ADMET study of ResD1 were carried out using AutoDock 4.2 and ADMETLab 2.0. ResD1 was evaluated for in vitro antioxidant, antimicrobial, anticancer, and CAXII gene expression as per the standard methods. Results: In silico molecular docking results revealed that ResD1 is capable of attaching to the ERα (estrogen receptor alpha) protein via hydrogen and hydrophobic bonds and has -7.12 kcal/mol as docking score. The novel derivative (IC50 = 42.8 μg/ml) exhibited better radical scavenging ability than ascorbic acid (control). The antimicrobial activities exemplify that it can induce microbial cell death for all the strains at higher concentrations. MTT assay results portrayed the potent antiproliferative activity against MCF-7 cell lines (IC50 = 155.2 μg/ml) and non-cytotoxicity for MDA-MB- 231 cell lines. Moreover, the synthesized resveratrol derivative induced ROS (reactive oxygen species) levels in MCF-7 cells, indicating cytotoxicity. CAXII gene expression study showed that it downregulated the CAXII genes. Conclusion: This study serves as an example of how a newly proposed resveratrol analogue might be utilized as a viable pharmacophore for specifically targeting the ER alpha protein which will be beneficial in investigating a fresh batch of effective resveratrol mimics as prospective anticancer agents.
Keywords: molecular docking